Cancer through black eyes - The views of UK based black men towards cancer: A constructivist grounded theory study. (August 2017) - Mulugeta, Betselot; Williamson, Susan; Monks, Rob; Hack, Thomas; Beaver, Kinta
Abstract: Purpose: Little is known about black African (BA) and black African-Caribbean (BAC) men's views towards cancer; yet culture and acculturation can contribute to the way in which people understand, explain and develop their attitudes towards cancer. Hence, cancer prevention and early detection strategies may not be sensitive to United Kingdom (UK)-based black men's views, affecting their awareness of risk factors and early detection services. This study explored the views of UK-based BA and BAC men towards cancer. Method: In collaboration with black community organisations based in four major cities in the UK, 25 participants were recruited using convenience and theoretical sampling methods. Data were collected using 33 semi-structured interviews, and analysed using grounded theory analytic procedures. Results: One core category (cancer through black eyes) and seven sub-categories emerged; 'cultural views', 'religious beliefs', 'avoiding Babylon', 'alienation', 'suspicious mind', 'advertisements and information influence very little', and 'gap in service provision (bridging the gap)'. Participants' views towards cancer were linked to socially constructed perspectives, linked with cultural and religious beliefs, and shaped by what being a black male means in society. Risk factors such as smoking and obesity had different meanings and symbolisation through black eyes. There were macro- and micro-level similarities and differences between BA and BAC men. Conclusions: Cancer services and related public-health campaigns aimed at black men need to understand cancer through black eyes. Public health campaigns based solely on the clinical meaning of cancer are incongruent with black men's understandings of cancer, and therefore ineffective at reducing health inequality. Highlights: What is already known about the topic: Prostate cancer disproportionately affects black men in both the UK and USA. Low levels of screening uptake are common for black men in the UK. The reasons why black men are less aware of cancer risk factors is unclear. Little is known about black men's understanding of cancer. What this paper adds: A theory of 'cancer through black eyes' was generated to understand black men's views towards cancer. Black men's views towards cancer were linked to their cultural and religious beliefs. Clinical risk factors such as smoking and obesity had different meanings and symbolisation through black eyes.